Inquiry-based Learning in English Teaching at a Candidate School of IB PYP: Implementation and Benefits - Heppy Mutammimah; Dewi Rochsantiningsih; Abdul Asib (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
This paper aimed to investigate the implementation of inquiry-based learning (IBL) in English teaching at candidate school of International Baccalaureate Primary Years Programme (IB PYP) in Surakarta and explore the benefits of its implementation in English teaching. Three English teachers at a candidate school of IB PYP in Surakarta participated in this study and they were chosen purposively. This research employed a qualitative approach and emphasized on a case study. The techniques for collecting data comprised in-depth interview and observation. The collected data were analyzed by the researchers through Constant Comparative Method (CCM). The results revealed that the implementation of inquiry-based learning in English teaching in this school used Bruce and Davidson's view and some features of IBL. That cycles involved asking, investigating, creating, discussing and reflecting. And the benefits of this method in English teaching based on IB PYP were 1) the teachers can create meaningful activities for the students, 2) teaching and learning were student-centered, 3) the students learn through language and get endurable understanding, and 4) it promotes students ’skills and attitude at teamwork.